Diseño de un prototipo electrónico para el control automático de la luz alta de un vehículo mediante detección inteligente de otros automóviles - Miranda-Arce, Ronald (Instituto Tecnológico de Costa Rica, 2018)
The design and testing of an electronic prototype for the automatic control of the vehicle's high light through the intelligent detection of other automobiles is presented. This improves driving experience and driving safety at night, reducing the risk of accidents due to glare on the roads. It exposes the use of machine learning for the training of a neural network, that allows deep recognition of patterns, in this case identify the pattern that describes a vehicle when it approaches. A neural network capable of correctly identifying up to 89% of the cases occurred in the tests performed was successfully trained, generating the signals to automatically control the high beam and low beam.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica). Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2018.
Keywords: Tecnología del aprendizaje; Vehículos; Tránsito de carreteras; Luz; Led; Salud; Visión; Sistemas electrónicos; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics; Research Subject Categories::TECHNOLOGY::Engineering mechanics::Vehicle engineering